A social protection and integration strategy for children of OFWs a case study on the psycho-social support program of BUNGA Foundation, Inc - Abenir, Mark Anthony D. (2010)
There is limited literature on how government and non-government agencies conduct psycho-social support programs and how effective these are in helping children left behind by overseas Filipino workers (OFWs). This paper addresses the gap by analyzing the ANAK program of BUNGA Foundation Inc. It makes use of auto-ethnography since it draws from the author's phenomenological experience as part of said Foundation for five years and as one who, from birth until graduation from high school, was an OFW child. Additional data gathering methods included desk review of documents, participant observation, and informal interviews with key informants.
The study describes the components of the ANAK program of BUNGA, some of its gains from the perspective of the children themselves, and deviations from the design. It found the program to have had positive effects on the children, particularly in helping them regain familiarity and intimacy with their parent(s) and positively manage psychosocial and emotional strains. However, the ANAK program needs improvement in terms of operationalizing the children's right to participation, and its involvement of teachers and parents left behind and other caregivers. Teachers and parents/caregivers represent basic pillars in ensuring a holistic approach to care drain, and program effectiveness and sustainability. Recommendations are given, specially on how children's right to participation can be fulfilled by reinforcing the organizing component of the ANAK program. A framework for organizing OFW children is part of the recommendations.